2021
DOI: 10.1093/biolinnean/blab077
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in activity, locomotion and behavioural complexity in tadpoles

Abstract: Metamorphosis is a widespread developmental process that involves considerable changes in morphology, habitat use, ecology and behaviour between early developmental (larval) stages and adult forms. Among amphibians, anuran larvae (tadpoles) undergo massive morphological and ecological changes during their development, with early stages characterized by somatic growth, whereas more conspicuous changes (i.e. metamorphosis) occur later during development. In this study, we examined how locomotor and behavioural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…However, given that trematodes rely on physical and chemical cues to locate their hosts (Combes et al, 1994 ; Haas, 2003 ), parasites may have responded to bluegill particularly given that tadpole activity was reduced with bluegill exposure, which may have made tadpoles less detectable. Across all treatments, we observed an increase in tadpole activity after week 4, which is likely attributable to changes in tadpole behavior with development, as larval anurans increase activity as they develop until they near metamorphosis (Cheron et al, 2021 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, given that trematodes rely on physical and chemical cues to locate their hosts (Combes et al, 1994 ; Haas, 2003 ), parasites may have responded to bluegill particularly given that tadpole activity was reduced with bluegill exposure, which may have made tadpoles less detectable. Across all treatments, we observed an increase in tadpole activity after week 4, which is likely attributable to changes in tadpole behavior with development, as larval anurans increase activity as they develop until they near metamorphosis (Cheron et al, 2021 ).…”
Section: Discussionmentioning
confidence: 78%
“…Across all treatments, we observed an increase in tadpole activity after week 4, which is likely attributable to changes in tadpole behavior with development, as larval anurans increase activity as they develop until they near metamorphosis (Cheron et al, 2021).…”
Section: Bluegill Predators Had the Greatest Impact On The Community ...mentioning
confidence: 78%
“…We found that females in better condition produced clutches with greater hatching success. In this species and its close relative B. bufo ( Trujillo et al 2017 ), hatching success has been either related to fertilization success ( Touzot et al 2020 ) or to embryonic mortality ( Cheron et al 2021b ). Our result demonstrates that the quality (body condition) of females positively influenced embryonic survival while our analyses revealed that male phenotype does not significantly affect hatching success.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some controversies about using faecal microbiome to reflect gut microbiome comprehensively (Tang et al, 2020), we still privileged this non-invasive sampling method to release the toadlets upon metamorphosis. During pre-metamorphic larval development, spined toad tadpoles are the most active swimming and feeding at Gosner stage 37 (Cheron et al, 2021), resulting in a more significant production of faeces. Therefore, we started sampling tadpoles’ faeces for gut microbiota analyses once they reached Gosner stage 37.…”
Section: Methodsmentioning
confidence: 99%
“…During pre-metamorphic larval development, spined toad tadpoles are the most active swimming and feeding at Gosner stage 37 (Cheron et al, 2021), resulting in a larger production of faeces. We therefore started sampling tadpoles' faeces for gut microbiota analyses once they reached Gosner stage 37.…”
Section: Faecal Sampling For Microbiome Analysesmentioning
confidence: 99%